Variasi Bentuk dan Nilai Emotif Disfemia dalam Penyajian Rubrik Opini pada Harian Kompas Online - Pratiwi, Dini Restiyanti; Soleh, Anjas Rusdiyanto; Rahmawati, Ida Yeni (Jurnal Pendidikan Bahasa dan Sastra, 2023)
This study aims to (1) identify forms of the use of dysphema in opinion articles found in Kompas Online daily and (2) map the emotive values arising from the use of dysphema in opinion articles found in Kompas Online daily. This type of research is descriptive-qualitative. The data in this study are opinion articles contained in the opinion rubric of the online Kompas daily. The data source in this study is the opinion rubric found on the page https://www.kompas.id/categories/opini/artikel-opini/. Collecting data in this study using the note-taking method. Data validation in this study uses theoretical triangulation. Data analysis in this study used an interactive analysis model or Miles and Huberman including: (1) data reduction; (2) data presentation; and (3) drawing conclusions or verification. The results obtained from this study concluded that the use of dysphema found 49 data, the four forms of dysphema namely 20 data of active verbs, 12 data of nouns, 9 data of passive verbs, and 8 data of adjectives. In addition, the taste or emotive values that arise from the use of dysphema are the values of feeling terrible, upsetting, and demeaning.